Fiber-based food packaging materials in view of bacterial growth and survival capacities - Schmid, Paul Jakob; Maitz, Stephanie; Plank, Nadine; Knaipp, Elisabeth; Pölzl, Sabine; Kittinger, Clemens (Frontiers in Microbiology, 2023)
Understanding interactions of bacteria with fiber-based packaging materials is fundamental for appropriate food packaging. We propose a laboratory model to evaluate microbial growth and survival in liquid media solely consisting of packaging materials with different fiber types. We evaluated food contaminating species (E. coli, S. aureus, B. cereus), two packaging material isolates and bacterial endospores for their growth abilities. Growth capacities differed substantially between the samples as well as between bacterial strains. Growth and survival were strongest for the packaging material entirely made of recycled fibers (secondary food packaging) with up to 10.8 log10 CFU/ml for the packaging isolates. Among the food contaminating species, B. cereus and E. coli could grow in the sample of entirely recycled fibers with maxima of 6.1 log10 and 8.6 log10 CFU/mL, respectively. E. coli was the only species that was able to grow in bleached fresh fibers up to 7.0 log10 CFU/mL. S. aureus perished in all samples and was undetectable after 1 to 6 days after inoculation, depending on the sample. The packaging material strains were isolated from recycled fibers and could grow only in samples containing recycled fibers, indicating an adaption to this environment. Spores germinated only in the completely recycled sample. Additionally, microbial digestion of cellulose and xylan might not be a crucial factor for growth. This is the first study describing bacterial growth in food packaging materials itself and proposing functionalization strategies towards active food packaging through pH-lowering.